Risk assessment of the influence of atmospheric air pollution in the Dniprо city on health of the population - Holovkova, T.A.; Shevchenko, O.A.; Hruzd, V.V. (Environment & Health, 2025)
The aim of the study - to analyze and assess the dynamics of atmospheric emissions and the content of pollutants in the surface layer of the atmosphere to determine the risk of the impact on health of the population of the city of Dnipro.Materials and methods. The volume of emissions from stationary sources of the Dnipropetrovsk region and the content of pollutants in the atmospheric air of Dnipro city for the five-year period from 2019 to 2023 were analyzed. To determine the danger of the manifestation of eco-dependent pathology due to the influence of atmospheric air pollution, the method of the risk assessing to public health was used with the calculation of the hazard ratio (HQ) and hazard index (NI) in the case of the combined effect of chemicals by inhalation.Results. Over the past five years, the volume of industrial emissions into the atmosphere of the Dnipropetrovsk region has fluctuated from 576.9 to 328.9 thousand tons per year, dynamic observations indicate a steady trend towards a decrease in the value of atmospheric emissions over the specified period to 33.2%. In the air of an industrial city, the following are constantly registered: dust, sulfur dioxide, carbon monoxide, nitrogen dioxide, nitrogen oxide, hydrogen sulfide, phenol, ammonia, formaldehyde. The average annual concentrations of the main air pollutants, such as sulfur dioxide, carbon monoxide, hydrogen sulfide, did not exceed the standards, the content of phenol and ammonia was determined at the maximum permissible level, and the concentrations of dust, nitrogen dioxide, nitrogen oxide and formaldehyde did not comply with the hygienic requirements for the entire observation period and significantly exceeded them, by 1.5-5.3 times. It was established that the permissible level of the hazard coefficient (HQ>1) for the health of the population of Dnipro, exposed to atmospheric air pollution, was exceeded. The hazard index of the development of non-carcinogenic effects (HI) for the population of Dnipro reached 14.43, which indicates the formation of a zone of high non-carcinogenic risk.Conclusions. Despite the decrease in atmospheric air emissions over the five-year observation period by 33%, significant pollution of the surface layer of the atmosphere of the city of Dnipro was established, the population of which is exposed to a high level of non-carcinogenic risk. The obtained data are a scientific and informational basis for the development of a set of sanitary and hygienic measures to prevent eco-dependent pathology among the population of the industrial region.
Keywords: atmospheric emissions; air pollution; chemical compounds; impact; risk; public health